The impact of participation: how civil society organisations contribute to the democratic quality of the UN world summit on the information society - Charlotte Dany (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2006)
The World Summit on the Information Society (WSIS) was held by the United Nations in 2003 to draft a programmatic declaration for the information age. The involvement of civil society organisations (CSOs) in the drafting process was innovative and led to WSIS becoming an especially instructive case in order to assess the potential of civil society participation in global governance. The author analyses the preconditions that were provided for CSOs to participate within this policy process and how it influenced the policy output. The all-encompassing rhetoric of the multi-stakeholder approach at WSIS and its good performance with regard to conceding access, transparency and inclusion to non-state actors suggest that the summit would be responsive to arguments from civil society and therefore a likely case for a deliberative policy process. However, the impact of CSOs on the policy documents has only been marginal. Despite favourable conditions for CSO participation, WSIS was not as responsive towards civil society arguments as could have been expected. A content analysis of policy documents and civil society statements with regard to three selected issue areas - Internet governance, intellectual property rights and communication rights - reveals that CSOs were, in many cases, not able to influence the outcome. Their argumentative input only led to minor changes in the policy documents. The case of the World Summit on the Information Society indicates that favourable conditions for CSO participation alone do not necessarily provide a solution for the democratic deficit in global governance.
Keywords: 320; Bürgerbeteiligung; Nichtregierungsorganisation; Informationspolitik; Welt